2009
DOI: 10.1038/onc.2009.309
|View full text |Cite
|
Sign up to set email alerts
|

HEY1 Leu94Met gene polymorphism dramatically modifies its biological functions

Abstract: The hairy/enhancer-of-split related with YRPW motif 1 (HEY1) is a member of the basic-helix-loop-helix-Orange (bHLH-O) family of transcriptional repressors that mediate Notch signaling. Several cancer-related pathways also regulate HEY1 expression, and HEY1 itself acts as an indirect positive regulator of the p53 tumor suppressor protein and a negative regulator of androgen receptor activity. In this study we show how a naturally occurring non-synonymous polymorphism at codon 94 of HEY1, which results in a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…9 In addition to these genetic studies, an expression analysis found that the majority of prostate samples showed total exclusion of HEY1 protein from the nucleus, 10 an abnormality that prevents HEY1-dependent p53 activation. 3 Thus, alterations in HEY1 function and/or expression could contribute to the oncogenic transformation, impairing the crosstalk between Notch and p53 or other signaling pathways.…”
Section: The Transcription Factor Crebzf Is a Novel Positive Regulatomentioning
confidence: 99%
See 1 more Smart Citation
“…9 In addition to these genetic studies, an expression analysis found that the majority of prostate samples showed total exclusion of HEY1 protein from the nucleus, 10 an abnormality that prevents HEY1-dependent p53 activation. 3 Thus, alterations in HEY1 function and/or expression could contribute to the oncogenic transformation, impairing the crosstalk between Notch and p53 or other signaling pathways.…”
Section: The Transcription Factor Crebzf Is a Novel Positive Regulatomentioning
confidence: 99%
“…1 Hairy/enhancer-of-split related with YRPW motif 1 (HEY1), a well-characterized effector within the Notch signaling, has been recently identified as a new p53 co-regulator. 2,3 Initially, a genome-wide functional analysis revealed that HEY1 is a positive regulator of p53 through repression of MDM2 transcription, although the detailed molecular mechanisms responsible for this regulation are still unknown. 2 Subsequently, our laboratory showed that HEY1 expression impairs cell proliferation in human osteosarcoma cells (U2OS) in a p53-dependent manner and sensitizes cells to p53-activating chemotherapeutic drugs.…”
Section: The Transcription Factor Crebzf Is a Novel Positive Regulatomentioning
confidence: 99%
“…For instance, nonsynonymous single-nucleotide polymorphism (SNP) naturally occurs at codon 94 of Hey1, which leads to a substitution of a leucine residue by methionine (L94M) in the helix 2 domain. The L94M-mutant Hey1 transforms from an androgen receptor corepressor to androgen receptor coactivator without changing its intrinsic repressive domains (14). The phosphorylation of the Serine-68 residue of Hey1 prevents its enhancement of p53 transcriptional activation but confers p53-activating chemotherapy resistance, whereas wild-type Hey1 stimulates p53 and alters the sensitivity to p53-activating chemotherapy drugs.…”
Section: Structure Of the Hey Family Proteinsmentioning
confidence: 99%
“…It should be noted that the specificity for protein interactions and target molecules of different Hey variants is differential between certain cell types. L94M Hey1 variant strongly interacts with Hey2, whereas Hey1 forms an unstable homodimer with Hey2 (14). There is a potential, unknown Hey1 variant enhancing matrix metallopeptidase 9 (MMP9) expression in osteosarcoma, whereas wild-type Hey1 is unable to bind to the MMP9 promoter itself (16).…”
Section: Structure Of the Hey Family Proteinsmentioning
confidence: 99%
See 1 more Smart Citation